Polionemobius gyirongensis sp. nov. from Tibet, China, and the identification of the species Polionemobius ebony Wu & Ma, 2022 and its close relative (Orthoptera: Trigonidiidae; Nemobiinae) - Wang, Rui; Ma, Li-Bin (Zootaxa, 2023)
A new species, Polionemobius gyirongensis Ma & Wang, sp. nov., is reported from Tibet, China. Its appearance is similar to that of Polionemobius yunnanus Liu & Shi, 2014, with a small-sized body and oval notch on both sides of the pronotum. Description and illustrations for the new species are provided here. At the same time, we compared Polionemobius ebony Wu & Ma, 2022 and Pteronemobius nigriscens (Shiraki, 1911) and determined that they are different species.